MicroRNA-520/373 family functions as a tumor suppressor in estrogen receptor negative breast cancer by targeting NF-[kappa]B and TGF-β signaling pathways - Keklikoglou, Ioanna; Körner, Cindy; Schneeweiss, Andreas; Şahin, Özgür; Wiemann, Stefan; Tschulena, Ulrich (Oncogene, 2012)
MicroRNAs (miRNAs) as modulators of gene expression have been described to display both tumor-promoting and tumor-suppressive functions. Although their role has been studied in different tumor types, little is known about how they regulate nuclear factor κB (NF-κB) signaling in breast cancer. Here, we performed an unbiased whole genome miRNA (miRome) screen to identify novel modulators of NF-κB pathway in breast cancer. The screen identified 13 miRNA families whose members induced consistent effects on NF-κB activity. Among those, the miR-520/373 family inhibited NF-κB signaling through direct targeting of RELA and thus strongly reduced expression and secretion of the pro-inflammatory cytokines interleukin (IL)-6 and IL-8. With a combination of in vitro and in vivo approaches, we propose a metastasis-suppressive role of miR-520/373 family. miR-520c and miR-373 abrogated both in vitro cell invasion and in vivo intravasation of highly invasive MDA-MB-231 cells. However, knockdown of RELA did not affect their metastatic ability. mRNA profiling of MDA-MB-231 cells on overexpression of miR-520/373 members revealed a strong downregulation of transforming growth factor-β (TGF-β) signaling. Mechanistically, the metastasis-suppressive role of miR-520/373 can be attributed to direct suppression of TGFBR2, as the silencing of TGFBR2 phenocopied the effects of miR-520/373 overexpression on suppression of Smad-dependent expression of the metastasis-promoting genes parathyroid hormone-related protein, plasminogen activator inhibitor-1 and angiopoietin-like 4 as well as tumor cell invasion, in vitro and in vivo. A negative correlation between miR-520c and TGFBR2 expression was observed in estrogen receptor negative (ER−) breast cancer patients but not in the ER positive (ER+) subtype. Remarkably, decreased expression of miR-520c correlated with lymph node metastasis specifically in ER− tumors. Taken together, our findings reveal that miR-520/373 family has a tumor-suppressive role in ER− breast cancer by acting as a link between the NF-κB and TGF-β pathways and may thus contribute to the interplay of tumor progression, metastasis and inflammation.